Pengaruh Kombinasi Silika dan Asam Humat terhadap Ketersediaan Nitrogen dan Pertumbuhan Tanaman Padi pada Tanah Berpasir - Rusyla Dwi Rahayu; Wanti Mindari; Moch. Arifin Moch. Arifin (Soilrens, 2021)
Sandy soils have high macropores and low nutrient availability. This condition is caused by the soil matrix which has no negative charge, so that nutrients are easily lost due to washing. Nitrogen loss has been reported to reduce rice production by 6.10%. The research aims to examine the application of humic acid and silica to increase the availability of nitrogen nutrients. Humic acid from compost and silica from rice husk is expected to increase the negative charge of the soil so that can adsorbnutrient ions such as nitrogen. The research was carried out from March to September 2021 in the greenhouse and laboratory of the Faculty of Agriculture, National Development University "Veteran" East Java. The research was structured using a factorial Completely Randomized Design (CRD). The first factor is silica dose with a level of 0 ton/ha, 0.5 ton/ha, 1 ton/ha, and 1.5 ton/ha. The second factor is the dose of humic acid with a level of 0 kg/ha, 20 kg/ha, 40 kg/ha, and 60 kg/ha. Observation parameters include the availability of N in the soil, the growth of rice plants which include plant length and the number of tillers. The results showed that the combination of humic acid and silica didn't significantly affect plant length and number of tillers, but had a significant effect on nitrogen availability. The best dose of the combination of silica with humic acid on nitrogen availability in sandy soils is S2H3 (Silica 1 ton/ha with humic acid 60 kg/ha).